Pengaruh Penerapan Green Human Resources Management Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Candra Nur Adiputra; Moh. Ja’far Sodiq Maksum (Lembaga Institute Development of Social Economic Cociety, 2026)
This study aims to examine the influence of Green Human Resources Management (GHRM) and the work environment on employee job satisfaction at CV Pangan Berkah Sentosa, Jombang Regency. A quantitative explanatory design was employed to test causal relationships among variables. The population consisted of 348 employees, with 186 respondents selected using Slovin’s formula at a 5% margin of error. Data were collected through structured Likert-scale questionnaires and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The findings indicate that GHRM does not have a significant effect on job satisfaction. In contrast, the work environment demonstrates a positive and statistically significant influence. Simultaneously, both variables significantly affect job satisfaction; however, the model explains only 8.6% of the variance. These results suggest that in a high-production operational context, tangible workplace conditions play a more dominant role in shaping employee satisfaction than sustainability-oriented HR practices. The study highlights the importance of improving workplace conditions as a strategic approach to enhance employee satisfaction, while emphasizing that GHRM implementation should be more integrative to generate meaningful psychological and organizational impacts.